Design of an Autonomous Social Orienting Training System (ASOTS) for Young Children with Autism - Zheng, Zhi (IEEE Trans Neural Syst Rehabil Eng, 2017)
Social communication is among the core areas of impairment for children with Autism Spectrum Disorders (ASD). The training of social orientation is important for improving social communication of children with ASD. In recent years, technology-assisted ASD intervention had gained momentum due to its potential advantages in terms of precision, sustainability, flexibility and cost. In this paper, we propose a closed-loop autonomous computer system, named ASOTS, for training social orientation skills to young children with ASD. This system is designed to detect and track a child’s attention in response to social orientation bids and help the child towards appropriate social orientation when needed. Response to name, an important social orientation skill, was used to demonstrate the functionality of the proposed system. Ten toddlers with ASD participated in a pilot user study to show whether the system could be used on young children who have been diagnosed with ASD. Another pilot user study with 10 TD infants tested whether this system has a potential to be applied for early detection for infants who were younger than the age when ASD diagnoses can be done. This was done intentionally to separately demonstrate utility and functionality for the clinical population of interest and to demonstrate functionality beyond current clinical identification capacity (i.e., infants). The results showed that the proposed system and the protocol were well tolerated by both groups, successfully captured young children’s attention, and elicited the desired behavior.